The infection spread model among grouped drug users - Tiešis, Vytautas (Lietuvos matematikos rinkinys, 1999)
The stochastic model of an infection spread among intravenous drug users was built in the case when a group of drug users shares one filled syringe. The impact of various factors to the rate of spread was investigated by the stochastic simulation.